Salvador - Didion, Joan (Simon & Schuster New York, 1983)
"Previously published in ... The New York review of books in October 1982." Discusses the situation of anarchy and terrorism in El Salvador as of 1982.
Keywords: Didion, Joan -- El Salvador; El Salvador; El Salvador; El Salvador; 1979-1992 -- El Salvador